1999
DOI: 10.1046/j.1365-2427.1999.00409.x
|View full text |Cite
|
Sign up to set email alerts
|

What happens to allochthonous material that falls into streams? A synthesis of new and published information from Coweeta

Abstract: 1. ,One of two things can happen to allochthonous material once it enters a stream: it can be broken down or it can be transported downstream. The efficiency with which allochthonous material is used is the result of these two opposing factors: breakdown and transport. 2. ,The present synthesis of new and published studies at Coweeta Hydrologic Laboratory compares biological use versus transport for four categories of particulate organic material: (1) large wood (logs); (2) small wood (sticks); (3) leaves; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
315
5
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 326 publications
(342 citation statements)
references
References 69 publications
15
315
5
7
Order By: Relevance
“…Our estimates of annual wood breakdown rates based on fungal assimilation alone (0.02 to 0.14 year Ϫ1 depending on wood size class and stream) are of the same order of magnitude as annual breakdown rates of hardwood sticks of similar diameter (0.5 to 3 cm) in stream decomposition experiments calculated from mass loss data (0.06 to 0.28 year Ϫ1 (11,18,40,55), underscoring fungal importance in submerged wood decomposition.…”
Section: Discussionsupporting
confidence: 60%
“…Our estimates of annual wood breakdown rates based on fungal assimilation alone (0.02 to 0.14 year Ϫ1 depending on wood size class and stream) are of the same order of magnitude as annual breakdown rates of hardwood sticks of similar diameter (0.5 to 3 cm) in stream decomposition experiments calculated from mass loss data (0.06 to 0.28 year Ϫ1 (11,18,40,55), underscoring fungal importance in submerged wood decomposition.…”
Section: Discussionsupporting
confidence: 60%
“…However, the magnitude of change in actual stream concentrations is probably much lower because leaf fall does not occur as a single pulse of uniform leaves. In deciduous forests of temperate areas of the world, leaf fall may be spread over several months and typically consists of a mixture of leaf species with different rates of conditioning and decay (e.g., CUMMINS et al, 1989;WEBSTER et al, 1999). Consequently, the effect of microbial uptake and mineralization in real streams should be much more subdued than we observed in these simulations.…”
Section: Do Microbial Processes On Decaying Leaves Modify Water Colummentioning
confidence: 82%
“…Many studies have suggested that breakdown of leaves occurs near where they fall into streams (e.g., WEBSTER et al, 1999). However, leaf breakdown includes fragmentation, leaching, animal consumption, and decay.…”
Section: Is There a Net Retention Or A Net Mineralization Of Nutrientmentioning
confidence: 99%
“…In each reach, we deployed traps every 20 m (n ϭ 10), 35 cm above the stream surface to collect pollen; microscope slides with exposed double-sided tape were anchored on each trap and deployed for 24 h. We collected two slides from each trap per day during pollen shed and stored slides in the dark until pollen counts were made by using fluorescence microscopy (ϫ40) (28). We calculated pollen input rates as grams of corn pollen deposited per meter squared streambed per day (Ϸ3.5 ϫ 10 6 corn pollen grains in 1 g).…”
Section: Methodsmentioning
confidence: 99%